2012
DOI: 10.1242/jcs.094060
|View full text |Cite
|
Sign up to set email alerts
|

The HIF1 target geneNOX2promotes angiogenesis through urotensin-II

Abstract: SummaryUrotensin-II (U-II) has been considered as one of the most potent vasoactive peptides, although its physiological and pathophysiological role is still not finally resolved. Recent evidence suggests that it promotes angiogenic responses in endothelial cells, although the underlying signalling mechanisms are unclear. Reactive oxygen species derived from NADPH oxidases are major signalling molecules in the vasculature. Because NOX2 is functional in endothelial cells, we investigated the role of the NOX2-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 36 publications
(45 reference statements)
3
55
1
Order By: Relevance
“…Using hypoxyprobe, we found that DOX induced hypoxic stress in cardiac tissue ( Figure 2A), which in turn led to increases in the abundance of hypoxia-inducible factor 1α (HIF1α) and heme oxygenase-1 (HO-1) in mouse hearts ( Figure 2, B and C). HIF1α is known to enhance production of ROS by increasing expression of Nox2 (28), and DOX also increased the abundance of Nox2 (Figure 2, B-D). The upregulation of Nox2 expression correlated well with the reduction in heart weight caused by DOX treatment ( Figure 2D).…”
Section: Resultsmentioning
confidence: 98%
“…Using hypoxyprobe, we found that DOX induced hypoxic stress in cardiac tissue ( Figure 2A), which in turn led to increases in the abundance of hypoxia-inducible factor 1α (HIF1α) and heme oxygenase-1 (HO-1) in mouse hearts ( Figure 2, B and C). HIF1α is known to enhance production of ROS by increasing expression of Nox2 (28), and DOX also increased the abundance of Nox2 (Figure 2, B-D). The upregulation of Nox2 expression correlated well with the reduction in heart weight caused by DOX treatment ( Figure 2D).…”
Section: Resultsmentioning
confidence: 98%
“…The ROSproducing NADPH oxidase Nox-2 is a target gene of HIF-1a, and, in turn, Nox-2-derived ROS promote HIF-1a expression (12,106). Though its cross-talk with HIF-1a suggests its role in stem cell self renewal, Nox-2 activity attributes to the phagocytosis ability of myeloid cells.…”
Section: Ros In Inflammationmentioning
confidence: 99%
“…37 Nox2 is a reactive oxygen species-producing enzyme known to be implicated in pathological angiogenesis. [38][39][40][41] Collectively, our findings suggest novel roles for endothelial PLD2 in regulating hypoxia-induced HIF-1α and downstream gene expression, which contribute to the cellular response of ECs to hypoxic stress and angiogenesis. This suggests that PLD2 is a modulator of EC functions during hypoxic stress and angiogenesis under pathological conditions.…”
Section: Discussionmentioning
confidence: 74%